Study of The Potential Development of Leading Tourist Areas in Binjai City - Muhammad Fachri Bin Zahari; Cut Nuraini; Abdi Sugiarto (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Tourism is a sector strategy in encouraging regional economic growth, cultural preservation, and improving community welfare. Binjai City, as one of the buffer areas of Medan Metropolitan, has a number of areas that have the potential to be developed into leading tourist destinations. However, un-til now there has been no directed and integrated development strategy for areas that have this potential.This research aims to identify and analyze the potential for the development of leading tourist areas in Binjai City through the Mixed Methods approach, which is a combination of qualitative and quantitative methods. The focus of the study is directed at three strategic areas, namely Taman Merdeka Binjai, the Binjai Grand Mosque Area, and the Jalan Veteran Culinary Village, which have strong historical, so-cio-cultural, and local economic potential but have not been optimally exploited.Data was collected through a survey of 150 respondents consisting of tourists, MSME actors, local communities, and government officials, as well as in-depth interviews with 12 key informants. The re-sults of the quantitative analysis showed that the attractiveness of the area and community support re-ceived the highest score in respondents' perception, while infrastructure and the use of digital technolo-gy are aspects that still require special attention. Qualitative analysis supports these findings, where vari-ous technical and institutional constraints are still found that hinder sustainable development.The results of data integration show that the potential for the development of leading tourist areas in Binjai City is quite high in terms of location, cultural value, and support from the local community. However, to realize a competitive region, strategic interventions are needed in the form of improving the quality of infrastructure, digitizing promotions, and collaboration between sectors. Policy recommenda-tions are filled with institutional capacity strengthening, community empowerment, and the establish-ment of tourism development programs based on local and sustainable potential.